(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
This paper presents the fundamentals of Analog to Digital Conversion using the Sigma Delta Modulation concept. It has been clearly shown how the process of Sigma Delta Conversion used in ADCs can achieve higher speeds even after employing Oversampling above Nyquist rate. The various parameters affecting the design and performance of the Delta Sigma employed ADC have been analyzed. Stability considerations of higher order sigma delta modulators have also been analyzed to attain an optimized approach to decide upon the design of the SDM. Variation in the SNR has been shown with changes in Over Sampling Rate